SISTEM PEMANTAUAN PARKIR MOBIL ONLINE MENGGUNAKAN WIRELESS SENSOR NETWORK (WSN) - Dadan Nurdin Bagenda (INSTITUT DIGITAL EKONOMI LPKIA, 2023)
Shopping places, tourist attractions and other public places of course have car parks. Several problems faced by visitors include the availability of parking spaces. This situation requires visitors to spend a lot of time in the process of searching for empty parking spaces due to the lack of direction regarding the availability of parking spaces in a parking lot. The aim of this research is to detect the availability of empty parking spaces and provide this information to visitors online which can be accessed via the Android application. The detection method used is measuring distance using an ultrasonic sensor using the wireless sensor network (WSN) method which is installed in each parking lot and sending the availability status via WiFi to a local server via an access point. The next process is that the local server will update the detected availability information to the online server or web server so that it can be accessed via the Android application. System test results show that the average time to send occupied status information to visitors' smartphones is 4.86 seconds and unoccupied 1.20 seconds.